Bimodal benefit for cochlear implant listeners with different grades of hearing loss in the opposite ear - Hoppe, Ulrich; Hocke, Thomas; Digeser, Frank (Acta Oto-Laryngologica, 2018)
OBJECTIVE: To determine speech perception in quiet and noise of adult cochlear implant listeners retaining a hearing aid contralaterally. Second, to investigate the influence of contralateral hearing thresholds and speech perception on bimodal hearing. PATIENTS AND METHODS: Sentence recognition with hearing aid alone, cochlear implant alone and bimodally at 6 months after cochlear implantation were assessed in 148 postlingually deafened adults. Data were analyzed for bimodal summation using measures of speech perception in quiet and in noise. RESULTS: Most of the subjects showed improved sentence recognition in quiet and in noise in the bimodal condition compared to the hearing aid-only or cochlear implant-only mode. The large variability of bimodal benefit in quiet can be partially explained by the degree of pure tone loss. Also, subjects with better hearing on the acoustic side experience significant benefit from the additional electrical input. CONCLUSIONS: Bimodal summation shows different characteristics in quiet and noise. Bimodal benefit in quiet depends on hearing thresholds at higher frequencies as well as in the lower- and middle-frequency ranges. For the bimodal benefit in noise, no correlation with hearing threshold in any frequency range was found.
EVALuna2:35458